Avaliação da neoformação óssea na sutura palatina mediana por meio de radiografia digitalizada após a expansão assistida cirurgicamente - Malmström, Márcia Ferreira Vasconcelos (2007)
OBJECTIVES: To evaluate the new bone formation at the midpalatal suture in adult patients submitted to surgically assisted rapid maxillary expansion. METHODS: Regular conventional occlusal radiographs were obtained from the initial stage up to 120 days and digitized with a scanner with transparency adapter for evaluation of optical density. RESULTS: The optical density presented an increase at the final stage of retention, yet the pixel values achieved at 120 days were significantly lower than the values of the initial stage. CONCLUSIONS: 1) the pixel values exhibited an individual variability in the process of suture remodeling; 2) there was no similarity of optical density between the final period of retention and the initial values, demonstrating that the 120-day period was not enough for complete new bone formation and bone remodeling at the suture; 3) the results achieved by the computerized method corresponded to the information achieved on the conventional occlusal radiographs, adding the quantitative analysis of the obtained data, and may be used as a complementary diagnostic method in the orthodontic clinic.